Ð”Ð¸ÑÐ»ÐµÐºÑ‚Ñ€Ð¸Ñ‡ÐµÑÐºÐ°Ñ Ð¿Ñ€Ð¾Ð½Ð¸Ñ†Ð°ÐµÐ¼Ð¾ÑÑ‚ÑŒ ÑÑÐºÑƒÐ»ÑÑ‚Ð¾Ð² Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° Ð¿Ñ€Ð¸ Ð½Ð¾Ñ€Ð¼Ð¾- Ð¸ Ð¿Ð°Ñ‚Ð¾ÑÐ¿ÐµÑ€Ð¼Ð¸Ð¸ Ð¿Ð¾ÑÐ»Ðµ Ð²Ð·Ð°Ð¸Ð¼Ð¾Ð´ÐµÐ¹ÑÑ‚Ð²Ð¸Ñ Ñ ÐºÑ€Ð¸Ð¾Ð·Ð°Ñ‰Ð¸Ñ‚Ð½Ð¾Ð¹ ÑÑ€ÐµÐ´Ð¾Ð¹ - Rodionova, V. L.; Tchoob, N. N.; Schegoleva, T. Yu.; Todorov, P. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
Using the SWF-dielectrometry the real ε′ and imaginary ε″parts of dielectric permittivity were shown to be changed depending on spermatogenesis pathology. A glycerol-lactose-yolk cryoprotective medium affects the state of the ejaculate water component, decreases the free water content in spermatozoa.